Lip Cream Formulation from Miana Leaf Extract (Coleus scutellarioides L.) As A Natural Dye - Vera Estefania Kaban; Nasri Nasri; Hariyadi Dharmawan Syahputra; Junius Gian Ginting (Nusantara Scientific Medical, 2023)
Abstrack The miana leaves (Coleus scutellarioides L.) contain flavonoids that can provide specific dyes. The purpose of the study was to formulate miana leaf extract in lip cream preparations as natural dyes. The use of natural lip cream dyes is a solution to overcome the problem of synthetic lip cream dyes. One of the plants such as the miana leaves contains secondary metabolites, one of which is flavonoids which can provide dyes. The natural colors found in miana leaves can be used as natural dyes in cosmetics. The purpose of the study was to determine at what concentration the miana leaves produced the most optimal physical quality of color in the preparation of lip cream. The method of the research includes the manufacture of ethanol extract of miana leaves (Coleus scutellarioides L.) by maceration for 5 days with 96% ethanol solvent and followed by remeseration with the same solvent. The extract formulas used were 5%, 10%, and 15%. The evaluations included organoleptic, homogeneity test, physical test, pH test, irritation test and color preference test. The results of the lip cream preparation, the results of the organoleptic examination were declared to have a semi-solid dosage form, a distinctive odor and varied colors F1, cream color, F2 salmon red, F3 brick red, homogeneity examination results were declared homogeneous, the results of observation of the preparation did not state that there was no change on the shape, color and odor of the preparation, the average pH test results were 4.1, the test results were declared non-irritating, the result of the color preference of the three formulas that the panelists preferred was a concentration of 15% because the color was clear and very soft. Miana leaf ethanol extract can be made as a colorant in lip cream preparations.